2004
DOI: 10.1086/424913
|View full text |Cite
|
Sign up to set email alerts
|

The Collimation‐corrected Gamma‐Ray Burst Energies Correlate with the Peak Energy of Their νFνSpectrum

Abstract: We consider all bursts with known redshift and F peak energy, E obs peak . For a good fraction of them an estimate of the jet opening angle is available from the achromatic break of their afterglow light curve. This allows the derivation of the collimation-corrected energy of the bursts, E . The distribution of the values of E is more spread out than in previous findings, covering about 2 orders of magnitude. We find a surprisingly tight correlation between E and the source frame E peak : E obs peak (1 þ z) / … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

64
904
6
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 674 publications
(978 citation statements)
references
References 64 publications
64
904
6
4
Order By: Relevance
“…We checked whether GRB 061201 satisfies the E p,i −E iso and E p,i − E γ correlations found for long GRBs (Amati et al 2002;Ghirlanda et al 2004), where E p,i is the intrinsic peak energy of the νF ν spectrum of the prompt emission. We find that, by rescaling the measured E p = 873 +458 −284 keV from Konus-Wind observations (Golenetskii et al 2006) at each proposed redshift for this burst, the isotropic and beaming corrected energy are several orders of magnitudes lower than the values predicted by the correlations.…”
Section: Discussionmentioning
confidence: 99%
“…We checked whether GRB 061201 satisfies the E p,i −E iso and E p,i − E γ correlations found for long GRBs (Amati et al 2002;Ghirlanda et al 2004), where E p,i is the intrinsic peak energy of the νF ν spectrum of the prompt emission. We find that, by rescaling the measured E p = 873 +458 −284 keV from Konus-Wind observations (Golenetskii et al 2006) at each proposed redshift for this burst, the isotropic and beaming corrected energy are several orders of magnitudes lower than the values predicted by the correlations.…”
Section: Discussionmentioning
confidence: 99%
“…However, statistical investigations of large samples of GRBs aim to find common characteristics and correlations that link individual events and therefore provide insight into the mechanisms common to GRBs. Statistical investigations performed so far have found a number of trends and correlations within and linking the prompt gamma-ray emission and the afterglow emission (e.g., Amati et al 2002;Ghirlanda, Ghisellini & Lazzati 2004;Dainotti, Cardone & Capozziello 2008;Panaitescu & Vestrand 2008;Bernardini et al 2012;D'Avanzo et al 2012;Li et al 2012;Liang et al 2013;Zaninoni et al 2013;Panaitescu, Vestrand & Woźniak 2013). Within the prompt gamma-ray emission, the most renowned correlation discovered is the Amati relation, a correlation between the isotropic γ-ray energy Eiso and the restframe γ-ray peak energy E peak (see Amati et al 2002, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Ghirlanda et al (2004) suggested that the maximum opening angle is about θ max = 24 o . In this paper, the opening angle for each GRB is generated randomly within θ < θ max .…”
Section: Samples and Equationsmentioning
confidence: 99%